Religiöse Erinnerungsorte in Ostmitteleuropa: Konstitution und Konkurrenz im nationen- und epochenübergreifenden Zugriff - Bahlcke, Joachim (Akad. Verl., 2013)
The handbook regards religion as a "cultural system" in two dimensions: both in terms of a point of depature that can add rigor to research projects informed by a new understanding of the history of remembrance; and as an impetus to examine the religious diversity of Central Europe as a key characteristic of this large region
Gesehen am 25.04.2017
Keywords: Aufsatzsammlung; Geschichte; Religion; Historische Stätte; Kollektives Gedächtnis; Ostmitteleuropa; Kirchengeschichte